2008
DOI: 10.1071/dn08066
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of an antinematicidal compound fromLeucaena leucocephala

Abstract: Abstract. Leucaena leucocephala is a small tropical tree used for a variety of purposes in agriculture, land management and homeopathic medicine. Quercetin, a flavonoid, was isolated and characterised from extracts of leaves of L. leucocephala and its effects on egg hatching and juvenile mortality of Meloidogyne incognita were investigated at 0.8, 0.4 and 0.2% in vitro. The compound was highly toxic to eggs and juveniles of the nematode at the three rates tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…The egg-laying activity in this study was also found to be significantly reduced after exposure to LL extract and mimosine, as demonstrated by the decrease in the mean number of eggs laid. Similar research findings concordantly showed the inhibition of egg-laying and -hatching post-treatment with LL extracts in different nematode species [ 30 , 32 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. For instance, a recent study by Romero et al (2020) [ 76 ] reported that the ethanolic extract of LL leaves significantly inhibited egg-hatching activity up to 54% in Haemonchus contortus.…”
Section: Discussionsupporting
confidence: 82%
“…The egg-laying activity in this study was also found to be significantly reduced after exposure to LL extract and mimosine, as demonstrated by the decrease in the mean number of eggs laid. Similar research findings concordantly showed the inhibition of egg-laying and -hatching post-treatment with LL extracts in different nematode species [ 30 , 32 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. For instance, a recent study by Romero et al (2020) [ 76 ] reported that the ethanolic extract of LL leaves significantly inhibited egg-hatching activity up to 54% in Haemonchus contortus.…”
Section: Discussionsupporting
confidence: 82%
“…The activity observed was substantiated by the presence of secondary metabolites in the extract of L. leucocephala. The nematicidal activity of quercertin a phenolic compound isolated from L. leucocephala was reiterated by Adekunle and Aderogba (2008). They reported a high level of toxicity to M. incognita eggs.…”
Section: Discussionmentioning
confidence: 99%
“…In field trials, crude extracts of Tephrosia purpurea were shown to significantly reduce root-galling in French bean ( Njenga et al, 2019 ); while extracts from T. cinerea stem were bioactive against M. incognita ( Cristóbal-Alejo et al, 2006 ). Additionally, extracts of roots and leaves of Leucaena leucocephala have been reported to contain flavonoids like quercetin known to be highly toxic to M. incognita ( Adekunle and Aderogba, 2008 ); Medicago sativa is also known to contain saponin mixture, with nematicidal potency reported against X. index , M. incognita , and G. rostochiensis ; and when amended in soil, significant population reductions were evident ( D’Addabbo et al, 2011 ).…”
Section: Composition Activity and Potency Of The Active Constituentsmentioning
confidence: 99%